Identification of the extreme daily maximum temperatures and their frequencies and intensities in Iraq - Hashim, Shiemaa A.; Ahmed, Muna H.; Al-Jiboori, Monim H.; Khanjer, Ebtesam F.; Tawfeek, Yasmin Q. (International Journal of Innovative Research and Scientific Studies, 2025)
Extreme maximum air temperature (ETmax) has significant impacts on ecosystems, human health, and socio-economic systems, especially in climate-vulnerable regions such as Iraq. The purpose of this study is to identify ETmax exceedances and analyze their frequency in six provinces of Iraq: Basra, Shanafiya, Baghdad, Rutba, Kirkuk, and Shakhan, using daily Tmax data obtained from NASA/POWER for 10 years (2014 to 2023). Using the 95th percentile method, thresholds of Tmax, their extreme temporal frequency, intensity, and annual trends were evaluated in four seasons: winter, spring, summer, and fall. Summer and spring show the highest thresholds (5.2%), with 50°C in Basra and Baghdad. The fall peak in Basra is 47°C (4.6%), while Rutba records the lowest thresholds in all seasons. Short-term exceedances (1-3 days) are common throughout Iraq, especially in winter, spring, and summer, while longer durations (>4 days) are rare but occur occasionally, with Rutba and Baghdad showing notable extended events. All regions except Shanafiya show an increasing trend in extreme Tmax exceedances, with Rutba and Kirkuk showing the largest increase (~1 day/year). Overall, Iraq shows an increasing trend in extreme Tmax events, driven by urbanization and climate dynamics. The national average shows an increase of ~0.66 day/year. The results underscore the increasing climate instability in Iraq and highlight regional disparities in exposure to extreme heat. Identifying ETmax in Iraq has critical practical implications in several sectors such as public health, agriculture, water resources, energy demand, urban heat, wildfires, economy, ecosystems, and disaster preparedness. This knowledge enables policymakers to develop effective mitigation and adaptation strategies.